Strategi Kepemimpinan Kepala Pusat Kegiatan Belajar Masyarakat dalam Mengembangkan Life Skiil (Studi Kasus Terhadap Suku Anak Dalam) di Kecamatan Bajubang - Muhammad Muhammad; Kaspul Anwar US; Sya`roni Sya`roni; Jamrizal Jamrizal; Sumirah Sumirah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This research is to discuss the leadership strategy of the head of the community learning activity center in developing life skills for the inner children in Bajubang District, Batang Hari Regency, as for the problems that can be encountered in this study are: how the leadership of the head of the community learning activity center in developing life skills for the inner tribe, how the strategy of the head of the community learning activity center in developing life skills These and what are the supporting and inhibiting factors in developing life skills for the Orang Rimba tribe? This research uses a qualitative approach by taking data derived from primary and secondary data through observation, interviews and documentation. Which is then analyzed using the usual stages so as to get the correct results efficiently. The results of this study are to answer the formulation of the problem that has been raised, with the hope that the results of this study can provide an explanation of the stages and strategies of a leader in developing life skills even in formal and non-formal education.